1989
DOI: 10.1620/tjem.159.153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute protein loads of different sources on renal function of patients with diabetic nephropathy.

Abstract: To evaluate effects of acute loading of different proteins on renal function, glomerular filtration rate (GFR), albumin excretion rate (AER), and concentrations of plasma amino acids, 11 normal volunteers and 20 diabetic patients were studied before and after eating 1.0 g/kg body weight of either tuna fish meal or bean curd on separate days. In normal subjects, the mean baseline GFR was 115.8+9.5 ml/min/1.73 m2, and the mean GFRs after ingestion of tuna fish meal were 134.1± 15.5 (1 hr), 146.2 + 18.8 (2 hr), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 22 publications
1
27
0
1
Order By: Relevance
“…Previous studies that demonstrated renal effects of protein in the diet used differing populations of subjects. Nakamura et al (14) found, in acute feeding studies, that individuals with type 1 or type 2 diabetes and microalbuminuria did not have a significant change in GFR during 3 h after eating tuna fish or bean curd (tofu). In nondiabetic individuals and individuals with diabetes and normoalbuminuria, there was a significant increase in GFR after tuna fish but not after tofu (12).…”
Section: Outcome Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies that demonstrated renal effects of protein in the diet used differing populations of subjects. Nakamura et al (14) found, in acute feeding studies, that individuals with type 1 or type 2 diabetes and microalbuminuria did not have a significant change in GFR during 3 h after eating tuna fish or bean curd (tofu). In nondiabetic individuals and individuals with diabetes and normoalbuminuria, there was a significant increase in GFR after tuna fish but not after tofu (12).…”
Section: Outcome Parametersmentioning
confidence: 99%
“…Studies performed in normoalbuminuric individuals with diabetes have suggested that changing the composition of the diet by altering the source of protein from animal to plant, either acutely in the setting of a standard test meal (12) or for up to 4 weeks (13), might produce beneficial renal effects. However, in another acute study, individuals with type 1 or type 2 diabetes and microalbuminuria showed no significant change in renal function when given plant-based protein (PP) versus animal-based protein (AP) (14).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…These facts led us to investigate whether diabetic nephropathy was influenced by the quality as well as the quantity of dietary protein. Our previous study showed that acute administration of vegetable proteins (at least of cooked soybean protein) did not increase GFR (Nakamura et al 1989). In addition, the present study demonstrates that ingestion of cheese or egg white does not induce hyperfiltration.…”
Section: Discussionmentioning
confidence: 94%
“…These findings, together with the finding that low-protein alimentation may have the abovementioned harmful side effects, led us to investigate whether diabetic nephropathy is influenced by the quality as well as the quantity of dietary protein. In a previous report, we examined the influence of proteins from two different sources on renal function in healthy volunteers and diabetic subjects (Nakamura et al 1989). Our study showed that ingestion of cooked soybean protein does not increase GFR.…”
mentioning
confidence: 99%